THE EVALUATION OF THE WOUND HEALING PROPERTIES OF METHANOLIC BARK EXTRACT OF SAMADERA INDICA GAERTNER IN VIVO: Evaluation of wound healing - PR, Deepa; P, RAMA BHAT; Rao S, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The exracts of Samadera indica used in traditional medicines for the treatment of skin diseases, rheumatism, cough and to kill head lice. The main objective of the present study was to evaluate the wound healing activity of methanolic bark extract of Samadera indica. Methods: The bark samples of were collected, allowed to shade dry for a week, then coarsely powdered and was extracted with methanol by soxhlation process. The extract was used for wound healing experiment using excision wound model. 18 healthy Wistar albino rats divided into three groups of six rats each with average body weight of 150-200 g were selected randomly for the study. ANOVA was used to compare the variation in the treatments in the result. The 1st group of animals are left as such for natural healing process as control, 2nd group of animals were treated with standard ointment betadien and 3rd group with the test drug methanolic bark ointment formulation. The methanolic extract in simple ointment base as mentioned above and betadien ointment were applied on the wound once a day for 16 days starting from the day of wounding. The percentage wound closure was observed on 4th, 8th, 12th and 16th post wounding day. Results: As for the group received methanolic bark extract for wound healing, fourth day wound mean diameter was 208.0±3.521, 8th day the wound mean diameter was 160.66±7.89, 12th day wound mean diameter was 87.5±5.8 and 16th day wound mean diameter was 22.5±5.12. Comparing to standard drug betadien the bark extract showed faster healing in terms of diameter of wound which was statistically signified. Conclusions: The results of the experiment revealed that there was marked decrease in wound diameter with every point of time the observation made indicating the effect of extract on progressive healing of wound. Samadera indica proved its wound healing potential of the plant extract which is due to the bioactive compounds and thus the study supports local folklore practitioners and tribal people for the use of plant in different ailments.